The effectivenes of layanan informasi using contextual teaching and learning (CTL) approach to degree of students pornography trends - Asmidaryani Asmidaryani; Firman Firman; Nurhizrah Gistituati (International Conferences on Educational, Social Sciences and Technology)
Nowadays, the trend of student pornography increases every year. An increase in pornographic tendencies is thought to be due to lack of information. Information can be obtained by students through guidance and counseling services in schools. Providing information services will be more effective by using various approaches. This study aims to identify the effectiveness of Layanan Informasi using the CTL approach in reducing the tendency of student pornography. This research used Quasi Experiment design with non equivalent control group design. The research subjects were 21 students in control group and 21 treatment group. The research instrument was student pornography tendency inventory with reliability 0.892 , and data were analyzed using Wilcoxon Signed Ranks Test and Kolmogorov-Smirnov Two Independent Samples. Based on the findings, layanan informasi used CTL approach effective to the reduction of the student pornography tendencies. Counselors are recommended to apply the CTL approach on reducing it.